2021
DOI: 10.3390/agriculture11100943
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Wild Relative Rootstocks on Eggplant Growth, Yield and Fruit Physicochemical Properties under Open Field Conditions

Abstract: Eggplant is an essential vegetable crop that is rich in health-related compounds, and the content of these compounds can be increased through grafting. It was reported that grafting with vigorous wild relatives’ rootstocks can improve eggplant’s fruit quality. The study was conducted to investigate the fruit yield, composition and physicochemical traits of Solanum melongena ME, CE, NE and TE scions grafted on wild relatives’ rootstocks of ST, SM and SI. The results show that a notable graft success (100%) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…For example, interspecific tomato rootstocks effectively increased fruit quality, contents of bioactive compounds, and yield of the high-value 'Corbarino' tomato landrace scion (Parisi et al 2022). Plant growth, yield, and fruit physicochemical properties of eggplant scions showed better performance when grafted on the wild related rootstock of eggplant (Musa et al 2021). Zhang et al (2021) reported that tomato grafting with nitrogen use efficiency (NUE) rootstock improved nitrogen absorption and utilization and increased yield production at different nitrogen levels.…”
Section: Introductionmentioning
confidence: 99%
“…For example, interspecific tomato rootstocks effectively increased fruit quality, contents of bioactive compounds, and yield of the high-value 'Corbarino' tomato landrace scion (Parisi et al 2022). Plant growth, yield, and fruit physicochemical properties of eggplant scions showed better performance when grafted on the wild related rootstock of eggplant (Musa et al 2021). Zhang et al (2021) reported that tomato grafting with nitrogen use efficiency (NUE) rootstock improved nitrogen absorption and utilization and increased yield production at different nitrogen levels.…”
Section: Introductionmentioning
confidence: 99%